Fusion with fission power amplification - Moiseenko, V.E.; Ågren, O.; Noack, K.; Fomin, S.P. (Вопросы атомной науки и техники, 2008)
A scheme of a sub-critical system driven by fusion neutrons from a stellarator-mirror device is considered. In addition, a power production scheme which uses fusion power amplification by depleted uranium mantle is discussed.